Risk Factors for Urgency Incontinence in Women Undergoing Stress Urinary Incontinence Surgery - Leslie M. Rickey; Liyuan Huang; David D. Rahn; Yvonne Hsu; Heather J. Litman; Elizabeth R. Mueller (Advances in Urology)
Objective. To determine baseline variables associated with urgency urinary incontinence (UUI) in women presenting for stress urinary incontinence (SUI) surgery. Methods. Baseline data from two randomized trials enrolling 1,252 women were analyzed: SISTEr (fascial sling versus Burch colposuspension) and TOMUS (retropubic versus transobturator midurethral sling). Demographic data, POP-Q measures, and validated measures of symptom severity and quality of life were collected. Charlson Comorbidity Index (CCI) and Patient Health Questionnaire-9 were measured in TOMUS. Multivariate models were constructed with UUI and symptom severity as outcomes. Results. Over two-thirds of subjects reported bothersome UUI at baseline. TOMUS patients with more comorbidities had higher UDI irritative scores (CCI score 0 = 39.4, CCI score 1 = 42.1, and CCI score 2+ = 51.0, P=0.0003), and higher depression scores were associated with more severe UUI. Smoking, parity, prior incontinence surgery/treatment, prolapse stage, and incontinence episode frequency were not independently associated with UUI. Conclusions. There were no modifiable risk factors identified for patient-reported UUI in women presenting for SUI surgery. However, the direct relationships between comorbidity level, depression, and worsening of UUI/urgency symptoms may represent targets for preoperative intervention. Further research is necessary to elucidate the pathophysiologic mechanisms that explain the associations between these medical conditions and bladder function.